2013
DOI: 10.1111/bjh.12427
|View full text |Cite
|
Sign up to set email alerts
|

The induction of immunogenic cell death by type II anti‐CD20 monoclonal antibodies has mechanistic differences compared with type I rituximab

Abstract: These authors are joint senior authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Although obinutuzumab can induce immunogenic cell death, 12 in this model enhanced NK cell-mediated ADCC may eradicate tumor before establishment of a tumor-specific CD8-mediated T-cell response. However, although IFNγ secreting tumor-specific CD8 + T cells were not detected post therapy, depletion of CD8 + T cells during the course of therapy appeared critical for generation of immunological memory as over half of these mice were not protected from rechallenge, in agreement with a previous report.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although obinutuzumab can induce immunogenic cell death, 12 in this model enhanced NK cell-mediated ADCC may eradicate tumor before establishment of a tumor-specific CD8-mediated T-cell response. However, although IFNγ secreting tumor-specific CD8 + T cells were not detected post therapy, depletion of CD8 + T cells during the course of therapy appeared critical for generation of immunological memory as over half of these mice were not protected from rechallenge, in agreement with a previous report.…”
Section: Discussionmentioning
confidence: 92%
“…11 Furthermore, we have demonstrated that obinutuzumab induces the release of damage-associated molecular pattern molecules, which can prime dendritic cell maturation and T-cell activation. 12 Recent data have demonstrated the importance of the tumor microenvironment in regulating T-cell responses, which has led to intense interest in manipulating the balance between positive immune-stimulatory signals and negative regulatory signals with immuno-modulatory agents. 13 …”
Section: Introductionmentioning
confidence: 99%
“…93 Moreover, few of these therapies can liberate co-stimulatory signals from cancer cells (required to make ADCP immunogenic), for example, rituximab causing release of the TLR agonist, HMGB1. 94,95 Overall, these results show that besides their targeted activities, ADCP can help antibody-based therapies to achieve the desirable 'off-target' induction of antitumour immunity (Figure 2). 93 This raises similar precedence for other immunotherapies targeted towards the cancer cells, that is, anti-PD-L1 antibodies.…”
Section: Regulated Necrosismentioning
confidence: 85%
“…Emerging data suggest a ''vaccination'' effect with anti-CD20 antibodies, whereby cell death enhances dendritic cell maturation and T-cell activation to produce an antilymphoma immune response [67]. ''Proof-of-principle'' data have demonstrated an increased level of FL idiotype-specific T cells relative to baseline after rituximab treatment in five FL patients [68].…”
Section: Preclinical Observations With Obinutuzumabmentioning
confidence: 99%